2016
DOI: 10.1183/13993003.00109-2016
|View full text |Cite
|
Sign up to set email alerts
|

What's it like to live with idiopathic pulmonary fibrosis? Ask the experts

Abstract: @ERSpublicationsSharing and informing IPF healthcare decisions through partnerships with patients and their caregivers http://ow.ly/YHp3XOver the last 5-7 years, an enlightened paradigm has emerged for clinical research. In it, patients are not simply "subjects" to be studied or numbers to be analysed; more than "key stakeholders", patients are increasingly (and justly) recognised as the soul and substance of clinical investigation [1]. Patient advocacy organisations have added significant momentum to this mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The importance of engaging patients in IPF care has gained increasing attention during the last several years ( 45 ). Recent qualitative studies have reported a need for better education about IPF, information about specific treatment options and palliative care, and access to specialist centers and specialist nurses.…”
Section: How To Integrate Personomics Into Personalized Medicinementioning
confidence: 99%
“…The importance of engaging patients in IPF care has gained increasing attention during the last several years ( 45 ). Recent qualitative studies have reported a need for better education about IPF, information about specific treatment options and palliative care, and access to specialist centers and specialist nurses.…”
Section: How To Integrate Personomics Into Personalized Medicinementioning
confidence: 99%